Analysis of Industry Collaboration, School Achievement, and Education Costs on the Competitiveness of Vocational High Schools with Strategic Management as a Moderating Variable (Case Study at Nusantara Wisata Respati Vocational High School, East Jakarta) - Fitranty, Sarah; Margono, Hery (MANAZHIM, 2025)
In selecting a vocational high school (SMK), parents and prospective students must make informed decisions that align with their preferences and aspirations. This aspect creates a competitive environment among SMKs in attracting students. Before competing with other schools, both SMA/SMK consider various advantages to enhance their competitiveness. This research aims to investigate the influence of Industry Collaboration, School Achievement, and Education Cost Competitiveness, and determine whether Strategic Management can moderate the relationship between Industry Collaboration, School Achievement, and Education Cost on Competitiveness. This study was conducted at SMK Nusantara Wisata Respati with 60 respondents. Data were analyzed quantitatively using Multiply regression analysis (MRA) using SPSS 24.0. The research findings indicate that industry collaboration, school achievement, and education costs do not significantly influence competitiveness. Meanwhile, strategic management can moderate the relationship between industry collaboration and school achievement on competitiveness, while strategic management does not significantly moderate the relationship between education cost and competitiveness.